2018
DOI: 10.1097/shk.0000000000000915
|View full text |Cite
|
Sign up to set email alerts
|

FN14 Blockade on Pulmonary Microvascular Endothelial Cells Improves the Outcome of Sepsis-Induced Acute Lung Injury

Abstract: Pulmonary microvascular leakage is one of the characteristics of blood-air barrier dysfunction in septic acute lung injury/acute respiratory distress syndrome (ALI/ARDS). Fibroblast growth factor-inducible 14 (Fn14) exerts diverse functions under certain circumstances. However, the role of Fn14 on the integrity of pulmonary microvascular endothelial cells (PMVECs) during sepsis remains unknown. Septic ALI was induced via cecal ligation and puncture (CLP). Fn14 expression on PMVECs was measured 24 h after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Recently, accumulating evidences have suggested that the pulmonary microvascular dysfunction was associated with the hyper-permeability which played a critical role in the occurrence and development of ALI/ARDS [ 19 ]. The pulmonary microvascular endothelium is consisted by a continuous monolayer of PMVECs which form the internal wall of microvessels; the integrity maintains the gas exchange and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accumulating evidences have suggested that the pulmonary microvascular dysfunction was associated with the hyper-permeability which played a critical role in the occurrence and development of ALI/ARDS [ 19 ]. The pulmonary microvascular endothelium is consisted by a continuous monolayer of PMVECs which form the internal wall of microvessels; the integrity maintains the gas exchange and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In the progress of sepsis, the intestinal pathogenic microorganisms and their toxins could enter the body circulation after the damage of intestinal barrier, thus causing systemic infections and MODS [38]. Studies have shown that the rst organ to be attacked is lung, and about half of sepsis patients have combined symptoms of ALI [11]. ALI is a serious respiratory disease with diffuse alveolar damage as the main pathological feature and 31.5% of patients with ALI are caused by non-pulmonary sepsis [39].…”
Section: Discussionmentioning
confidence: 99%
“…The most vulnerable sites of sepsis infection are lung (64%), abdominal cavity (20%), blood (15%), kidney and urogenital tract (14%) [8]. Studies have shown that the rst organ to be attacked in the progress of MODS is lung, and 50% of sepsis patients have combined symptoms of ALI with poor prognosis [11]. At the same time, ALI is also an independent risk factor for organ failure and death in patients with sepsis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are required to verify this presumption. Zou et al [10] found that levels of Fn14 were upregulated on pulmonary microvascular endothelial cells in murine sepsis-induced acute lung injury/acute respiratory distress syndrome. Previous studies also revealed that concentrations of CD163 increased acutely during inflammation and macrophage activation due to metalloproteinase mediated cleavage near the macrophage membrane [19].…”
Section: Discussionmentioning
confidence: 99%
“…Through binding to its receptor fibroblast growth factor-inducible 14 (Fn14), TWEAK involves many biologic effects including tissue repair-associated processes, e.g., cell proliferation, cell migration, and angiogenesis, as well as the activation of proinflammatory signaling pathways [8, 9]. The low expression of Fn14 in normal tissues and over expression when injuries occur reveals a special role for TWEAK/Fn14 pathway in inflammation [10]. In terms of the activating effect of TWEAK on proinflammatory cytokines (IL-8, IL-6, etc. )…”
Section: Introductionmentioning
confidence: 99%